Exploring Organoleptic, Chemical, and Physical Properties of Foxtail Millet (Setaria italica) and Snakehead Fish (Channa striata) Cookies as Emergency Food Alternatives - Widiati, Aloisia Lovy; Astutik, Rini Duwi; Abbas, Marwati; Nastaina, Hayu Iyaka; Widyanto, Rahma Micho (Indonesian Journal of Human Nutrition, 2023)
High disaster risk in Indonesia necessitates the development of emergency food products (EFP). One potential EFP is cookies made from foxtail millet and snakehead fish. This study aimed to examine the sensory, chemical, and physical properties of EFP cookies with different formulations. This research used a completely randomized design. Variations in the composition of wheat flour, foxtail millet flour, and snakehead fish flour were P0(100:0:0), P1(8:76:16), P2(8:66:26), and P3(8:56:36). All treatments were analyzed for organoleptic quality using hedonic tests and proximate analysis, water activity analysis using an aw meter, and physical quality analysis using tensile strength. The Zeleny method was applied to identify the most optimal treatment, revealing that P1 emerged as the best formulation. P1 has the color, aroma, and taste that the panelists like, while maintaining a neutral rating in texture. P1 contains 241.51 kcal/50 grams of energy, 10.97% protein, 41.16% fat, 47.86% carbohydrates, 1.93% ash content, 4.93% water content, 0.55 water activity, and 17.16 N breaking strength. These results are in accordance with EFP and SNI 2973:2011 standards. The recommended daily consumption is 18 pieces (each piece weighing 25 grams) if not accompanied by any other food, or only 4-5 pieces if consumed as a snack.